(untitled) (Seminar_BG, 2025)
Thе article examines urban gardening as a practice of dwelling in the postsocialist Bulgarian city. Drawing on long-term anthropological fieldwork conducted in the Trakia housing district in Plovdiv, the study explores how inter-block gardens and peripheral “rancho” plots are maintained, transformed, and transmitted over time under shifting regimes of urban governance, property, and regulation. Urban gardens are approached as heterotopic and heterochronic spaces in which different practices of care, appropriation, and civic engagement overlap. The analysis demonstrates how repeated practices of planting, maintenance, and protection enable residents to transform abstract public space into lived place. From this perspective, urban gardening is understood as a durable mechanism of urban rootedness and as an analytical lens for understanding postsocialist modes of dwelling and the negotiation of public space. Argüelles, L., Anguelovski, I., & Dinnie, E. (2017). Power and privilege in alternative civic practices: Examining imaginaries of change and embedded rationalities in community economies. Geoforum, 86, 30–41. https://doi.org/10.1016/j.geoforum.2017.08.013 Axinte, A., Rafanell, C., and Iancu, B. (2025). Commoning the gardens by the Bloc. Informal gardening practices in the collective housing districts of a post-socialist city. Environmental Sociology, 11(4), 426–437. https://doi.org/10.1080/23251042.2025.2500727. Balázs, B. (2018). Community-building through food self-provisioning in Central and Eastern Europe: An analysis through the food commons framework. In J. L. Vivero-Pol et al. (eds.), Routledge handbook of food as a commons (pp. 480–493). London: Routledge. https://doi.org/10.4324/9781315161495 Baudry, S. (2010). Cultiver son jardin, s’inscrire dans la ville : Approche anthropologique des community gardens de New York City. Paris: Université Paris-Diderot – Paris VII. https://tel.archives-ouvertes.fr/tel-00962486 [20.12.2025]. Bellows, A. (2004). One hundred years of allotment gardens in Poland. Food & Foodways, 12(4), 247–276. https://doi.org/10.1080/07409710490893793 Bourdieu, P. (1977). Outline of Theory of Practice. Cambridge: Cambridge University Press. https://doi.org/10.1017/CBO9780511812507 Bourdieu, P. (1980). Le mort saisit le vif. Actes de la recherche en sciences sociales, 32–33, 3–14. https://doi.org/10.3406/arss.1980.2077 Bourdieu, P. (1986). The Forms of Capital. In J. Richardson (ed.), Handbook for the Sociology of Education (pp. 241–258). New York: Greenwood Press. Brenner, N., Peck, J., and Theodore, N. (2010). After neoliberalization?, Globalizations, 7(3), 327–345. Bundzhulov, A. (2003). Kakvo vaznikva na myastoto na? Izkustveni stavi i mrezhi pri sotsializma. Sotsiologicheski problemi, 1–2, 87–105. Daněk, P., Jehlička, P., and Smith, J. (2022). Urban gardening as multifunctional practice: Food, leisure and care. Geoforum, 128, 1–10. Deyanov, D. (2003). Obshtestvoto na mrezhite i sotsioanaliza na dara (Pierre Bourdieu i Ivo Možný). Sotsiologicheski problemi, 1–2, 72–86. Ditchev, I. (2003). Usyadaneto na nomadskiya komunizam. Sotsialisticheskata urbanizatsiya i formite na grazhdanstvo. Sotsiologicheski problemi, 3–4, 33–63. Ditchev, I. (2005). Prostranstva na zhelanieto, zhelanie za prostranstvo. Sofia: LIK. Djokić, V., et al. (2018). Everyday practices in socialist housing estates: Informality and appropriation of space. Cities, 74, 20–28. Foucault, M. (1986). Of Other Spaces (trans. Jay Miskowiec). Diacritics, 16(1), 22–27. https://doi.org/10.2307/464648 Foucault, M. (1998). Nadzor i nakazanie. Razhdaneto na zatvora. Sofia: Universitetsko izdatelstvo “Sv. Kliment Ohridski”. Galoș, D., and S. Medeșan. (2022). From Temporary Spatial Practices to Permanent Architectural Forms.The Case of “La Terenuri” from Mănăștur Neighborhood, Cluj-Napoca. Studies in History and Theory of Architecture, 10, 169–178. https://doi.org/10.54508/sITA.10.13. Gill, S. E., Handley, J. F., Ennos, A. R., and Pauleit, S. (2007). Adapting cities for climate change: The role of green infrastructure. Built Environment, 33(1), 115–133. Lefebvre, H. (2000). La production de l’espace. Paris: Anthropos. Mauss, M. (2001). Darat. Forma i osnovanie za obmena v arhaichnite obshtestva. Sofia: Kritika i humanizam. McClintock, N. (2014). Radical, reformist, and garden-variety neoliberal: Coming to terms with urban agriculture’s contradictions. Local Environment, 19(2), 147–171. Nikolova, N., and Georgieva, M. (2003). Vaplatenata istoriya na nastoyashteto: transformatsiya na mrezhovite kapitali. Sotsiologicheski problemi, 1–2, 217–234. Parusheva, D., Marcheva, I., and Zlatkova, M. (2010). Tinkering in Daily Life: People, State and Social(ist) Housing in Bulgaria. Études balkaniques, 3, 69–91. Petrov, P., and Ganeva-Raycheva, V. (eds.). (2021). Rasteniya i hora: Priblizheniya kam biokulturnite vrazki. Sofia: Institut za etnologiya i folkloristika s Etnografski muzey – BAN. Pickard, D. (2020). Naglasi na mestnata vlast i grazhdanskite aktori za razvitieto na Sofia kato zelen grad chrez gradsko zemedelie. Sotsiologicheski problemi, 52(2), 575–595. Pickard, D., Koleva, G., Draganova, M., Chengelova, E., Nakova, A., Stoyanova, Z., Tsvetkov, P., and Toleva-Nowak, N. (Eds.). (2022). Urban agriculture for improving the quality of life: Examples from Bulgaria. Springer Nature Switzerland AG. https://doi.org/10.1007/978-3-030-94742-2 Raychev, A. (2003). Genezis, mutatsiya i degeneratsiya na vtorite mrezhi. Sotsiologicheski problemi, 1–2, 5–13. Sovová, L., and Krylová, R. (2019). The Countryside in the City? Rural-Urban Dynamics in Allotment Gardens in Brno, Czech Republic. Moravian Geographical Reports 27(2): 108–121. https://doi.org/10.2478/mgr-2019-0009. Sukarev, V. (2023). Plovdivskata obshtina i izgrazhdaneto na gradskata i turisticheskata infrastruktura, 1944–1990 g. Prouchvane varhu institutsionalnata, stopanskata i vseкидневnata istoriya na Plovdiv. Plovdiv: Akademichno izdatelstvo na AU – Plovdiv. Țânțaș, M. D. (2012). Grădinar de București. Grădinile urbane din cartierul Pajura – studiu de caz. Master diss., Bucharest: Școala Națională de Studii Politice și Administrative, Facultatea de Ştiinte Politice. Zlatkova, M. (2012). Etnosotsiologiya na grada. Po primera na grad Plovdiv. Plovdiv: Universitetsko izdatelstvo “Paisii Hilendarski”. Zlatkova, M. (2015). Gardening the City: Neighbourliness and appropriation of the common spaces in Bulgaria. Colloquia Humanistica, 57, 41–60. https://doi.org/10.11649/ch.2015.012 Zrnić, V. (2018). City-making through urban gardening: public space and civic engagement in Zagreb (with T. Rubić), Narodna umjetnost, 55(1), 159-179.